7b-2+3b=30+6b

Simple and best practice solution for 7b-2+3b=30+6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7b-2+3b=30+6b equation:


Simplifying
7b + -2 + 3b = 30 + 6b

Reorder the terms:
-2 + 7b + 3b = 30 + 6b

Combine like terms: 7b + 3b = 10b
-2 + 10b = 30 + 6b

Solving
-2 + 10b = 30 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
-2 + 10b + -6b = 30 + 6b + -6b

Combine like terms: 10b + -6b = 4b
-2 + 4b = 30 + 6b + -6b

Combine like terms: 6b + -6b = 0
-2 + 4b = 30 + 0
-2 + 4b = 30

Add '2' to each side of the equation.
-2 + 2 + 4b = 30 + 2

Combine like terms: -2 + 2 = 0
0 + 4b = 30 + 2
4b = 30 + 2

Combine like terms: 30 + 2 = 32
4b = 32

Divide each side by '4'.
b = 8

Simplifying
b = 8

See similar equations:

| 4x=4096 | | -13-3z=12-4y | | y+14=3y+2 | | x-7*x*450=0 | | 0.16(36-24x)=0.66 | | 2x=1024 | | 2.5+8= | | z*3=2*(z+1) | | 7(9n+9)=315 | | 2x+4.5=21 | | 18x^2+216=0 | | ax+bk=t | | z*3=2*z+1 | | 7x^2-12x^2+5=0 | | 20-5m=45 | | -6a-(4b-12a+7c)= | | 2(2+3x)+2(2x-1)=3(x+6) | | 729=0 | | 7x+37=149 | | 5c+4=(-26) | | 9t+17=-1 | | 8t-9+4t=59-5t | | x+7=31 | | (x+14)+(3x-18)=180 | | (9x+2)+(2x)=90 | | 7(7-1*1)=42 | | 9(7t+6)=306 | | 15-10t+7+8t= | | -4(x+3)(x+3)+5=-8 | | 7x-7x-1=42 | | 68-5= | | x^2+19x+29=5x-4 |

Equations solver categories